Esthetic crown lengthening treatment on the maxillary anterior teeth - Wahjuningrum, Dian Agustin; Sampoerno, Galih; Prasetyo, Eric Priyo; Saraswati, Widya; Setyabudi; Saravanan, Pravinna; Riyadi, Tiara Lathifah; Ambarwati, Venny Lusanda (Universitas Airlangga, 2024)
Background: Asymmetrical smile design due to uneven gingival margin heights of the anterior upper teeth can lead to aesthetic issues and inadequate crown restorations, necessitating crown lengthening treatment. Purpose: The objective of this case report is to demonstrate the outcomes of crown lengthening to achieve improved aesthetics and symmetric gingival margin heights. Case: A 16-year-old female patient sought treatment for decayed left maxillary anterior teeth. Clinical examination revealed a non-vital tooth (tooth 21) with decay and excessively low gingival margins, along with asymmetrical gingival heights between the incisors and canines. Radiographs indicated radiolucent mass in the pulp chamber. Case Management: Crown lengthening was performed on teeth 12, 11, 21, and 22, and apexification was conducted on tooth 21 using a customized fiber post and lithium disilicate crown. Follow-up evaluations showed no complaints, well-maintained crowns, and healthy gingiva. Conclusion: Crown lengthening is feasible for anterior teeth with low gingival margins, enhancing clinical crown length to support aesthetic and final restorations in maxillary anterior teeth.